Natural contamination with mycotoxins produced by Fusarium graminearum and Fusarium poae in malting barley in Argentina - Nogueira, María Soledad (2018)
Two of the most common species of toxin-producing Fusarium contaminating small cereal grains are Fusarium graminearum and F. poae; with both elaborating diverse toxins, especially deoxynivalenol (DON) and nivalenol (NIV), respectively. The objective of our work during the 2012 through 2014 growing seasons was to screen crops for the most commonly isolated Fusarium species and to quantify DON and NIV toxins in natural malting-barley samples from different producing areas of Argentina. We identified 1,180 Fusarium isolates in the 119 samples analyzed, with 51.2% being F. graminearum, 26.2% as F. poae and 22.6% to other species. We found high concentrations of mycotoxins, at maximum values of 12 µg/g of DON and 7.71 µg/g of NIV. Of the samples, 23% exhibited DON at an average of 2.36 µg/g, with 44% exceeding the maximum limits (average of 5.24 µg/g); 29% contained NIV at an average of 2.36 µg/g; 7% contained both DON and NIV; and 55% were without DON or NIV. Finally, we report the mycotoxin contamination of the grain samples produced by F. graminearum and F. poae, those being the most frequent Fusarium species present. We identified the main Fusarium species affecting natural malting-barley grains in Argentina and documented the presence of a large number of samples with elevated concentrations of DON and NIV. To our knowledge, the investigation reported here was the first to quantify the contamination by Fusarium and its toxins in natural samples of malting barley in Argentina.